2016
DOI: 10.1007/s10021-016-0085-9
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Release of Carbon Dioxide from Arctic Tundra Ecosystems in Alaska

Abstract: Releases of the greenhouse gases carbon dioxide (CO2) and methane (CH4) from thawing permafrost are expected to be among the largest feedbacks to climate from arctic ecosystems. However, the current net carbon (C) balance of terrestrial arctic ecosystems is unknown. Recent studies suggest that these ecosystems are sources, sinks, or approximately in balance at present. Increases in air temperature and soil temperatures at all depths may trigger a new trajectory of CO2 release, which will be a significant feedb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
134
3
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(161 citation statements)
references
References 49 publications
11
134
3
1
Order By: Relevance
“…CC BY 4.0 License. loops (Post et al, 1982;Elberling et al, 2008;Chae et al, 2015;Christiansen, 2016;Euskirchen et al, 2016). In this study, the 2016 growing season saw the wetland plot shift from being an early season source to a late season sink.…”
Section: Comparing the Influence Of Abiotic Conditions And Nitrogen Amentioning
confidence: 68%
See 2 more Smart Citations
“…CC BY 4.0 License. loops (Post et al, 1982;Elberling et al, 2008;Chae et al, 2015;Christiansen, 2016;Euskirchen et al, 2016). In this study, the 2016 growing season saw the wetland plot shift from being an early season source to a late season sink.…”
Section: Comparing the Influence Of Abiotic Conditions And Nitrogen Amentioning
confidence: 68%
“…Short-term studies of Arctic tundra environments are suggesting that Arctic permafrost regions currently act as sinks of atmospheric and terrestrial C (Nobrega and Grogan, 2008;Lafleur et al, 2012;McGuire et al, 2012); however, the comprehensive C study by McGuire et al (2012) also determined 10 that the tundra has been neutral in recent decades. Generally, long-term C studies are still lacking across the High Arctic tundra (Euskirchen et al, 2016). A long-term study by Euskirchen et al (2016) found that increases in air and soil temperatures at multiple depths may trigger a new trajectory of CO2 release.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The measurements and data processing are described in more detail for Imnavait in [25] and for Bonanza Creek in [26]. For all the sites, the 30-minute values were aggregated into 24-hour values (averages for T; totals for P, and ET) using MATLAB.…”
Section: Methodsmentioning
confidence: 99%
“…et al, 1973;Laidler and Treitz, 2003). However, soil attributes can be equally important in ecosystem carbon exchange (Euskirchen et al, 2017), and it is crucial to find out how soil attributes co-vary with those plant attributes that can be detected using remote sensing. Moreover, while LAI is a suitable measure of photosynthetically-active biomass for vascular plants, few studies have produced LAI estimates for mosses (Bond-Lamberty and Gower, 2007) and the abundance of mosses has been estimated as areal coverage or thickness of the active green layer (Douma et al, 2007;5 Riutta et al, 2007).…”
Section: Introductionmentioning
confidence: 99%